PENERAPAN ADAPTIVE STATISTICAL ITTERATIVE RECONSTRUCTION PADA PERBAIKAN KUALITAS CITRA DAN DOSIS CT SCAN CHEST - Marido Bisra; Gatot Murti Wibowo; Agung Nugroho Setiawan (LPPM STIKes Awal Bros Pekanbaru, 2022)
The Filtered Back Projection (FBP) algorithm has been the standard algorithm for image reconstruction in computed tomography (CT) for many years, but it creates possible streak artifacts and a notable increase in image noise when radiation dose is reduced exceedingly. With technological advancement and increased computational capacities in workstations,Adaptive Statistical iterative reconstruction (ASIR) algorithms have reemerged as a potential alternative. The purpose of this review is to establish if there is a general consensus that ASIR algorithms faithfully reduce radiation dose and improve image quality in CT in comparison with the FBP algorithm. A systematic review of the literature from 2011 to 2022 was conducted using Elsevier, Google Scholar, Pubmed, AJR, dan Science Direct, Physica Medica and the Korean Journal of Radiology. A total of 11 articles were categorized as either synopsis articles or performance evaluation clinical studies. The results show that the use of IR algorithms reduces objective image noise, and at least preserves spatial resolution and low contrast detectability, even when dose is reduced. In conclusion, there is a general that ASIR algorithms can faithfully reduce radiation dose but must notice about ASIR level to improve image quality in CT in comparison with the FBP algorithm.